An explanatory sequential mixed method study of nursing students’ self-efficacy in caring for older adults in Ghana - Diana Abudu-Birresborn; Martine Puts; Lynn McCleary; Charlene H. Chu; Vida Yakong; Lisa Cranley (PLoS ONE, 2025)
Background There is considerable evidence indicating that nursing students demonstrate inadequate knowledge and negative attitudes toward working with older adults. This suggests nursing student’s unpreparedness to provide care for the expanding older adult population. Feelings of unpreparedness can negatively impact their motivation and confidence. However, limited evidence exists about how nursing students’ knowledge and attitudes influence their self-efficacy in caring for older adults. Knowing this can help to identify gaps and opportunities to facilitate nursing students’ confidence in caring for older adults in acute care settings. Aim To examine nursing students’ knowledge, attitudes, and self-efficacy and how these variables impact nursing student self-efficacy in caring for older adults in acute care settings in Ghana. Methods We employed explanatory sequential mixed method approach. In Phase I, we used a cross-sectional design and collected quantitative data about students’ knowledge, attitudes, and self-efficacy. Data were collected from 170 second and third-year nursing students between December 2019--March 2020. We analyzed the data using descriptive and multiple-variable linear regression. Survey results informed the selection of students for Phase II based on their scores. In Phase II, 17 nursing students were purposively selected for semi-structured interviews between November and December 2020. Interviews were transcribed and analyzed using thematic analysis. Both results were integrated and presented. Results Students’ mean age was 21 years (SD = 3.73). Just over half were female (54%). The majority had lived with/were currently living with older adults (83.0%). Many had low knowledge scores (71%) and a majority had positive attitudes (91%) and high self-efficacy scores (97%). Nursing students’ ages and attitudes were significantly positively associated with their self-efficacy. There was no significant association between students’ gerontology knowledge and self-efficacy. Qualitative findings showed that low knowledge scores were due to limited attention to gerontology education in the curriculum and heavy course load. Sociocultural norms in caring for older adults influenced students’ positive attitudes. This facilitated students’ interactions with older adults and increased their confidence. Higher self-efficacy scores were associated with the impact of the general nursing program, students’ perceived familiarity with the needs of older adults and routine procedural knowledge. Younger students perceived that their age and competencies were questioned by older adults, impacting their self-efficacy. Both datasets converged at integration. Conclusion It is imperative to enhance students’ knowledge and leverage their self-efficacy to advance gerontological nursing education and practice in Ghana.